2023
DOI: 10.3390/ijms24055017
|View full text |Cite
|
Sign up to set email alerts
|

Function and Evolution of the Loop Extrusion Machinery in Animals

Abstract: Structural maintenance of chromosomes (SMC) complexes are essential proteins found in genomes of all cellular organisms. Essential functions of these proteins, such as mitotic chromosome formation and sister chromatid cohesion, were discovered a long time ago. Recent advances in chromatin biology showed that SMC proteins are involved in many other genomic processes, acting as active motors extruding DNA, which leads to the formation of chromatin loops. Some loops formed by SMC proteins are highly cell type and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 179 publications
0
11
0
Order By: Relevance
“…For example, research has shown that gene expression can be influenced by variants situated hundreds or even millions of base pairs distant from the promoter. This can be attributed to processes such as loop extrusion [49] and other 3D-genomic mechanisms [50]. There are several strategies to address this constraint in GENA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research has shown that gene expression can be influenced by variants situated hundreds or even millions of base pairs distant from the promoter. This can be attributed to processes such as loop extrusion [49] and other 3D-genomic mechanisms [50]. There are several strategies to address this constraint in GENA.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin architectural proteins play a crucial role in maintaining the three-dimensional structure of the genome (Kabirova et al, 2023). Among them, special attention is drawn to the cohesin and condensin complexes belonging to the SMC (structural maintenance of chromosomes) family of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial architecture of interphase chromosomes has been demonstrated to be nonrandom, with chromatin all along partitioned into topologically associating domains (TADs), shaped by the extruding activity of cohesin 5 . CTCF, a DNA binding protein, halts cohesin extrusion at CTCF binding sites, thereby forming TAD boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive research, there are conflicting findings regarding the functional significance of TAD boundaries. While it is evident that some boundary disruptions can cause disease, not all alterations result in detectable phenotypic abnormalities 5 , 7 . Although computational models capable of predicting chromatin contact alterations for specified chromosomal rearrangements exist 8 , they currently do not offer a level of interpretation suitable for clinical application 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%